2018
DOI: 10.1159/000488419
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cgkii Suppresses Seizure Activity and Hippocampal Excitation by Regulating the Postsynaptic Delivery of Glua1

Abstract: Background/Aims: The imbalance between excitation and inhibition is a defining feature of epilepsy. GluA1 is an AMPA receptor subunit that can strengthen excitatory synaptic transmission when upregulated in the postsynaptic membrane, which has been implicated in the pathogenesis of epilepsy. cGKII, a cGMP-dependent protein kinase, regulates the GluA1 levels at the plasma membrane. Methods: To explore the role of cGKII in epilepsy, we investigated the expression of cGKII in patients with temporal lobe epilepsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…After blocking with 5% skim milk for 2 hours, the membrane was incubated with primary antibody overnight: Rac1 (1:500, sc-514583, Santa Cruz Biotechnology), Tiam1 (1:500, sc-393315, Santa Cruz Biotechnology), α-chimaerin (1:500, sc-365985, Santa Cruz Biotechnology), Bcr (1:500, sc-104, Santa Cruz Biotechnology), GluR-1 (1:500, sc-13152, Santa Cruz Biotechnology), Synapsin 1(1:500, ab254349, Abcam), and PSD-95 (1:500, sc-32290, Santa Cruz Biotechnology). The speci city of these primary antibodies has been veri ed (Mao et al 2017;Liu et al 2018;Elzinga et al 2013;Gu et al 2018;Groh et al 2014;Tsai et al 2012). The membrane was incubated with a mixture of anti-rabbit IgG (Golden Bridge, Zhongshan, China) and horseradish peroxidase (HRP) for 1 hour at room temperature.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…After blocking with 5% skim milk for 2 hours, the membrane was incubated with primary antibody overnight: Rac1 (1:500, sc-514583, Santa Cruz Biotechnology), Tiam1 (1:500, sc-393315, Santa Cruz Biotechnology), α-chimaerin (1:500, sc-365985, Santa Cruz Biotechnology), Bcr (1:500, sc-104, Santa Cruz Biotechnology), GluR-1 (1:500, sc-13152, Santa Cruz Biotechnology), Synapsin 1(1:500, ab254349, Abcam), and PSD-95 (1:500, sc-32290, Santa Cruz Biotechnology). The speci city of these primary antibodies has been veri ed (Mao et al 2017;Liu et al 2018;Elzinga et al 2013;Gu et al 2018;Groh et al 2014;Tsai et al 2012). The membrane was incubated with a mixture of anti-rabbit IgG (Golden Bridge, Zhongshan, China) and horseradish peroxidase (HRP) for 1 hour at room temperature.…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…It was previously reported that actin dynamics regulate AMPA receptor trafficking during synaptic plasticity and reverse the decrease in GluA1 levels in the hippocampus, which was shown to be dysregulated in an epilepsy model. 13 , 14 Therefore, we hypothesize that inhibition of S6K1 activity in chronic epileptic rats may modulate local translation and affect synaptic function and morphology, thereby correcting the multiple phenotypes displayed by epileptic rats.…”
Section: Introductionmentioning
confidence: 99%